An open‐source population balance modeling framework for the simulation of polydisperse multiphase flows. Issue 3 (16th December 2021) - Lehnigk, Ronald; Bainbridge, William; Liao, Yixiang; Lucas, Dirk; Niemi, Timo; Peltola, Juho; Schlegel, Fabian
Abstract: Polydispersity is a challenging feature of many industrial and environmental multiphase flows, influencing all related transfer and transport processes. Besides their size, the fluid or solid particles may be distributed with respect to other properties such as their velocity or shape. Here, a population balance model based on the method of classes is combined with a multifluid solver within the open source computational fluid dynamics library OpenFOAM. The model allows for tracking the evolution of one or more size‐conditioned secondary properties. It is applied to two different problems, the first being bubbly flow of air and water in a vertical pipe, where considering the velocity as a secondary property allows to resolve the size‐dependent radial segregation. The second application is the gas phase synthesis of titania powder, where non‐spherical particle aggregates appear whose shape is modeled through a collision diameter, leading to an improved prediction of the size distribution.